Rosiglitazone-induced CD36 up-regulation resolves inflammation by PPARγ and 5-LO-dependent pathways. Issue 4 (12th December 2013) - Ballesteros, Iván; Cuartero, María I; Pradillo, Jesús M; de la Parra, Juan; Pérez-Ruiz, Alberto; Corbí, Ángel; Ricote, Mercedes; Hamilton, John A; Sobrado, Mónica; Vivancos, José; Nombela, Florentino; Lizasoain, Ignacio; et al.
Abstract : PPARγ activation with RSG induces 5-LO-dependent CD36 expression in resident microglia that participates in resolution of inflammation by phagocytosis, in an experimental model of stroke. Abstract: PPARγ-achieved neuroprotection in experimental stroke has been explained by the inhibition of inflammatory genes, an action in which 5-LO, Alox5, is involved. In addition, PPARγ is known to promote the expression of CD36, a scavenger receptor that binds lipoproteins and mediates bacterial recognition and also phagocytosis. As phagocytic clearance of neutrophils is a requisite for resolution of the inflammatory response, PPARγ-induced CD36 expression might help to limit inflammatory tissue injury in stroke, an effect in which 5-LO might also be involved. Homogenates, sections, and cellular suspensions were prepared from brains of WT and Alox5 −/− mice exposed to distal pMCAO. BMMs were obtained from Lys-M Cre + PPARγ f/f and Lys-M Cre − PPARγ f/f mice. Stereological counting of double-immunofluorescence-labeled brain sections and FACS analysis of cell suspensions was performed. In vivo and in vitro phagocytosis of neutrophils by microglia/macrophages was analyzed. PPARγ activation with RSG induced CD36 expression in resident microglia. This process was mediated by the 5-LO gene, which is induced in neurons by PPARγ activation and at least by one of its products—LXA4 —which induced CD36 independently of PPARγ. Moreover, CD36 expression helped resolution of inflammation through phagocytosis, concomitantly to neuroprotection. Based on these findings, in addition to a direct modulation by PPARγ, we propose in brain a paracrine model by which products generated by neuronal 5-LO, such as LXA4, increase the microglial expression of CD36 and promote tissue repair in pathologies with an inflammatory component, such as stroke.